Wafer‐Scale Fabrication of High‐Performance n‐Type Polymer Monolayer Transistors Using a Multi‐Level Self‐Assembly Strategy. Issue 7 (14th December 2018) - Yao, Ze‐Fan; Zheng, Yu‐Qing; Li, Qi‐Yi; Lei, Ting; Zhang, Song; Zou, Lin; Liu, Han‐Yu; Dou, Jin‐Hu; Lu, Yang; Wang, Jie‐Yu; Gu, Xiaodan; Pei, Jian
Abstract: Wafer‐scale fabrication of high‐performance uniform organic electronic materials is of great challenge and has rarely been realized before. Previous large‐scale fabrication methods always lead to different layer thickness and thereby poor film and device uniformity. Herein, the first demonstration of 4 in. wafer‐scale, uniform, and high‐performance n‐type polymer monolayer films is reported, enabled by controlling the multi‐level self‐assembly process of conjugated polymers in solution. Since the self‐assembly process happened in solution, the uniform 2D polymer monolayers can be facilely deposited on various substrates, and theoretically without size limitations. Polymer monolayer transistors exhibit high electron mobilities of up to 1.88 cm 2 V −1 s −1, which is among the highest in n‐type monolayer organic transistors. This method allows to easily fabricate n‐type conjugated polymers with wafer‐scale, high uniformity, low contact resistance, and excellent transistor performance (better than the traditional spin‐coating method). This work provides an effective strategy to prepare large‐scale and uniform 2D polymer monolayers, which could enable the application of conjugated polymers for wafer‐scale sophisticated electronics. Abstract : Using a multi‐level self‐assembly strategy, an n‐type polymer monolayer field‐effect transistor is obtained on wafer‐scale. These devices offers high performance, high air‐stability, and high uniformity. The strategy enhances the formation of wafer‐scale and uniform polymer monolayers. Transistor arrays on a 4 in. wafer exhibit electron mobilities of up to 1.88 cm 2 V −1 s −1, among the highest reported until now for n‐type monolayer organic transistors.